(untitled) (Cadernos de Sociomuseologia, 2019)
In the context of the Museology of Scientific Research, in recent decades, it has gained more importance as the themes and approaches connect with socio-cultural and political-economic realities. This article approaches an investigation in the field of sociomuseology and how it articulates with some of the challenges of contemporaneity and what are their articulations with local and international contexts. Therefore, it aims at a better understanding of the issues that impact on contemporary society and, consequently, in the area of ​​Museology. During the most recent period of a change in the Museology sector, sociomology research has been expanded both in the breadth of approaches and topics addressed, as well as in the new threats that feed back the work done. The article will be based on the reflection and practice of the Ibero-American Museum, but whenever possible from an understanding of a broader context. Keywords: Sociomuseology, Museology, Research, Research, Contemporary.